Association of disability with long-term noncompliance of breast cancer screening. Issue 28 (1st October 2022) - Tak, Hyo Jung; Lee, Min Sok; Shih, Ya-Chen Tina
Abstract : 118 Background: Although the U.S. Preventive Services Task Force (USPSTF) recommends a biennial screening mammography for women aged 50 to 74 years at average risk for breast cancer, 24.6% of screening-eligible women do not follow the recommendation. Very little is known regarding the association between various types of disabilities and subsequent breast cancer screening behaviors following the initiation of screening mammography. This study examines the association of disability with short-term vs. long-term noncompliance of having a mammogram. Methods: Using data from 2016, 2018, and 2020 Behavioral Risk Factor Surveillance System annual surveys, we constructed the study cohort of women aged 55 to 74 years who did not have a cancer history and who received a mammogram at least once in the past. Outcomes are short-term (2 years) and long-term (5 years) noncompliance of USPSTF recommendations. Key independent variables are six binary variables of standard functional disability conditions (hearing, vision, cognition, ambulation, self-care, and independent living) in the first model and a categorized total number of disabilities (0, 1, 2, ≥3) in the second model. We employed a multivariable logistic regression model, adjusting individuals' socio-demographics, general health status, chronic conditions, health risk factors, and metropolitan statistical areas (MSA), and accounting for complex survey design. Results: Among the study cohort (n = 232, 143; weighted n = 29, 358, 431), 18.1% and 7.1% of women reported not having mammography in the past two and five years, respectively, representing short- vs. long-term noncompliance. Of the study cohort, 32.8% had any type of disability (ambulation 22.7%, cognition 11.0%, independent living 8.8%). Notably, the long-term noncompliance rate was highest among women with a disability and residing in non-MSA (10.2%). In multivariable analysis, while only disability in independent living was associated with short-term noncompliance (odds ratio [OR] 1.28; 95% confidence interval [CI] 1.15-1.42), disability in independent living (OR 1.34; 95% CI 1.18-1.52), vision (OR 1.15; 95% CI 1.01-1.32) and ambulation (OR 1.12; 95% CI 1.01-1.24) were all significantly associated with long-term noncompliance. Women with ≥3 disabilities were 1.64 times more likely to be non-compliant in the long term, and the association of disability with noncompliance was more pronounced in non-MSA. Conclusions: This study provides the first empirical evidence on the positive association between disability and screening noncompliance, especially in the long term. It suggests disability could aggravate disparities in timely access to cancer screening, particularly in non-MSA. Understanding how various types of disabilities affect screening behavior is a critical step for public health efforts in cancer prevention and control through identifying vulnerable subgroups for targeted interventions.